CLIL 教學運用在國小四年級數學科的行動研究 Using the Content and Language Integrated Learning (CLIL) Approach to Teach Elementary Fourth Grade Mathematics: An Action Research - 鍾羽雯 Yu-Wen Chung; 詹惠雪 Hui-Hsueh Chan (National Changhua University of Education, 2024)
行政院通過雙語國家政策後，許多縣市選擇CLIL為主要雙語教學模式，本研究透過教學行動研究反思與修正的歷程，建構可行的數學CLIL教學模式。研究者設計角度及三角形兩個幾何單元的教學，於110年10月6日至28日在國小四年級實施，蒐集教室觀察紀錄、訪談、文件資料、省思札記、中、英語單元成就測驗等資料，進行綜合分析。本研究主要發現如下：一、CLIL的學習情境可視學生需求提供中文輔助，課堂融入70 %的英語，並採異質分組促進同儕溝通互動。二、課程設計可依學科內容設計不同難度的操作活動與統整型的素養任務。三、教學實施可調整數學教科書活動安排，將相同數學概念整併，規劃符合CLIL內容和語言循環的教學活動。四、學習評量在課堂中著重英語聽和說形成性評量，課堂最後回到中文數學課本習題檢核數學概念。五、全班學生數學表現穩定，未因CLIL教學影響學習成效，但三角形單元的單字與句型較為複雜，學生學習仍受語言影響。 After the Executive Yuan passed the "Bilingual Nation 2030" policy, many county and city governments chose content and language integrated learning（CLIL）as their primary bilingual teaching model. This study constructed a practicable CLIL mathematics teaching model through reflection and revision of teaching action research. Two geometry units on angles and triangles were designed and implemented in a fourth-grade elementary school class from October 6-28, 2021. Data collected for analysis included classroom observations, interviews, documents, personal journals and achievement tests in Chinese and English. The findings showed that 1. CLIL learning contexts can provide Chinese as needed to student, integrate English into 70 % of each lesson, and arrange heterogeneous groupings to promote peer communication and interaction; 2. curriculum design can include hands-on activities and integrated literacy assignments with different levels of difficulty according to the content; 3. teaching implementation can adjust the arrangement of mathematics textbook activities, integrate the same mathematical concepts, and plan according to the CLIL content and language cycle; 4. learning assessment focuses on English listening and speaking formative assessments in the classroom and returns to the Chinese mathematics textbook exercises to check mathematical concepts and 5. students' performance in mathematics was stable and unaffected by the CLIL instruction, but the English words and sentences in the triangle unit were more complicated, and the students' learning was affected by the language.